2010
DOI: 10.1002/lary.21640
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillar Carcinoma in the Contralateral Tonsil

Abstract: A small population of patients with unilateral tonsil carcinoma will developed a second in the contralateral tonsil. This raises the question of whether removal of the contralateral tonsil at the time of initial treatment might have spared the morbidity/mortality of the subsequent contralateral tonsil cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Moreover, given that other 3 cases of bilateral synchronous tonsillar cancer in patients with SCCUP have been reported in studies that did not meet the inclusion criteria, we believe that the true incidence of bilateral/contralateral tumors is underestimated. 11,35,64 Bilateral tonsillar resection is further supported by this review, mainly for oncological reasons, but also by the fact that of 204 bilateral tonsillectomies performed (on a total of 416) only 2 bleeding episodes are reported in one 60 of the included articles, which did not specify if the source site was the tonsillar fossa or the base of tongue. Therefore, it seems clear that the advantage of finding the primary tumor largely outweighs the very minimal risks associated with the bilateral tonsillectomy procedure.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, given that other 3 cases of bilateral synchronous tonsillar cancer in patients with SCCUP have been reported in studies that did not meet the inclusion criteria, we believe that the true incidence of bilateral/contralateral tumors is underestimated. 11,35,64 Bilateral tonsillar resection is further supported by this review, mainly for oncological reasons, but also by the fact that of 204 bilateral tonsillectomies performed (on a total of 416) only 2 bleeding episodes are reported in one 60 of the included articles, which did not specify if the source site was the tonsillar fossa or the base of tongue. Therefore, it seems clear that the advantage of finding the primary tumor largely outweighs the very minimal risks associated with the bilateral tonsillectomy procedure.…”
Section: Discussionmentioning
confidence: 92%
“…Literature search identified 1035 studies (Figure ); after scrutinizing titles and abstracts, 1003 were excluded as non‐relevant, concerning other diseases, duplicates, non‐original studies, or non‐English studies. Forty‐two articles, which included palatine tonsillectomy in the diagnostic approach of SCCUP, were screened in full‐text: 4 studies were from the same institution, more precisely 2 from the University of Florida College of Medicine and 1 from The Johns Hopkins Hospital, and another 1 from the University of Pittsburgh Medical Center, which subsequently published 3 updated series included in the review; 4 studies contained non‐SCC histopathology; 6 studies have not reported enough information about the negativity of the physical examination and/or conventional cross‐sectional imaging carried out before tonsillectomy; 3 studies using TLM as surgical approach to the palatine tonsil were lacking data on the state of conventional imaging before EUA or on tonsillectomies performed; 7 studies did not specify the number of tonsillectomies performed; 2 studies had suspicious findings on physical examination and/or conventional cross‐sectional imaging carried out before TORS tonsillectomy; 1 was an anatomopathological study without any clinical information on patients involved; and 1 study conducted palatine tonsillectomy before conventional imaging. Excluded studies and respective reasons of exclusion are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge on additional contralateral synchronous tonsillar malignancy is crucial for avoidance of early recurrence of oropharyngeal cancer in patients with TC. Furthermore, radical treatment of such recurrences is commonly impossible, and five‐year survival rates are dramatically decreased in these patients . In Denmark, TCs are treated with radiotherapy or chemo‐radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the contralateral palatine and lingual tonsils can be the culprit in less the 10%. [2][3][4] Human papilloma virus (HPV) related oropharyngeal squamous cell carcinoma (OPSCC) comprises about 70% of all OPSCC cases and therefore the majority of the carcinoma of unknown primary (CUP) cases. 5 Primary site identification is important to focus therapy and limit morbidity.…”
Section: Introductionmentioning
confidence: 99%